Funding primary health care service delivery in the West Nile sub-region, Uganda (Commonwealth Journal of Local Governance, 2023)
The provision of primary health care services is a global concern and quality health service delivery is based on a number of factors, including motivated health workers, good-quality infrastructure, consistent supply of medicines and technologies, adequate funding, sound health plans, and evidence-based policies. This study investigated the funding of primary health care service delivery in three local government districts in Uganda’s West Nile sub-region, and identified deficiencies in the allocation, disbursement and timeliness of health funding which have a negative impact on service delivery. Inadequate funding affects the quality of services, limits essential supplies and causes excessive reliance on private financing, which is not sustainable in poor rural economies. In view of these findings, the study recommended deliberate action by both central government and district councils to increase the percentage of funding allocated in their annual budgets to the health sector, in line with the 2001 Abuja Declaration. The government of Uganda should consider prioritising an increase in total national budget allocations to local governments; primary health care disbursements from central government should be paid on time directly to health facilities by use of the ‘straight-through processing system’ for all types of funding; the government should introduce, support and encourage additional community financing initiatives such as Community Health Insurance Schemes; and district and local community leaders should be sensitised on the benefits of this approach.